From Tradition to Therapy: Plectranthus amboinicus as a Remedy for Respiratory Inflammation - Phattayanon, Natharin; Assawamakin, Anunchai; Dechwongya, Panudda; Dadookel, Assawin (Interprofessional Journal of Health Sciences, 2024)
The respiratory tract is the anatomical pathway through which air travels during respiration and plays a critical role in gas exchange. While inflammation is a necessary immune response for combating infections in this system, severe inflammation can be detrimental and even fatal. Pathogenic microorganisms frequently expose the respiratory tract, necessitating a prompt and robust immune response, particularly through inflammation, to swiftly eliminate these threats. To reduce the intensity and duration of pulmonary inflammation, extensive research has been conducted to explore the pathophysiological mechanisms and therapeutic strategies associated with lung inflammation. Among these strategies, natural products have garnered significant attention for their chemical composition and pharmacologic properties, particularly their potential therapeutic applications in treating respiratory inflammation. Traditional herbal remedies widely use Plectranthus amboinicus because of its effectiveness in reducing respiratory inflammation. Numerous studies have demonstrated the potential of this plant for treating pulmonary disorders because of its phytochemical and pharmacognostic properties, specifically the activity of its essential compounds against airway inflammation. This review focuses on the phytochemistry, extraction techniques, phytocompound analyses, pharmacological activities in respiratory disorders, and clinical efficacy of P. amboinicus as a conventional herbal treatment for lung inflammation.